Application of Analytical Chemistry to Foods and Food Technology - Naviglio, Daniele; Gallo, Monica (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
The application of analytical chemistry to the food sector allows the determination of the chemical composition of foods and the properties of their constituents, contributing to the definition of their nutritional and commodity value. Furthermore, it is possible to study the chemical modifications that food constituents undergo as a result of the treatments they undergo (food technology). Food analysis, therefore, allows us not only to determine the quality of a product or its nutritional value, but also to reveal adulterations and identify the presence of xenobiotic substances potentially harmful to human health. Furthermore, some foods, especially those of plant origin, contain numerous substances with beneficial effects on health. While these functional compounds can be obtained from a correct diet, they can also be extracted from food matrices for the formulation of nutraceutical products or added to foods by technological or biotechnological means for the production of functional foods. On the other hand, the enormous growth of the food industry over the last 50 years has broadened the field of application of analytical chemistry to encompass not only food but also food technology, which is fundamental for increasing the production of all types of food.